2018
DOI: 10.1159/000493456
|View full text |Cite
|
Sign up to set email alerts
|

Rac Regulates the TRAP-Induced Release of Phosphorylated-HSP27 from Human Platelets via p38 MAP Kinase but Not JNK

Abstract: Background/Aims: Thrombin induces the activation of human platelets through protease-activated receptor (PAR) 1 and PAR4, and Rac, a member of the Rho family of small GTPases, is implicated in PAR activation. We previously reported that phosphorylated-heat shock protein 27 (HSP27) is released from the thrombin receptor-activating peptide (TRAP)-stimulated platelets of diabetic patients. In the present study, we investigated the role of Rac in the TRAP-elicited release of phosphorylated-HSP27 from human platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Akt plays a crucial role in platelet activation-induced signaling of GPCRs [26]. Moreover, it has been shown that p38 MAP kinase is implicated in TRAP-stimulated platelets [27].…”
Section: Discussionmentioning
confidence: 99%
“…Akt plays a crucial role in platelet activation-induced signaling of GPCRs [26]. Moreover, it has been shown that p38 MAP kinase is implicated in TRAP-stimulated platelets [27].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that TRAP-induced phosphorylation of p38 MAP kinase, but not JNK, is followed by the phosphorylation of HSP27, leading to the release of phosphorylated HSP27 into the plasma [16] and that Akt in addition to p38 MAP kinase positively regulates the TRAP-induced release of phosphorylated HSP27 from human platelets in patients with DM [17]. Thus, we examined the effect of Aβ on TRAP-induced phosphorylation of Akt and HSP27 in human platelets.…”
Section: Effect Of Aβ On Trap-induced Phosphorylation Of Akt and Hsp2...mentioning
confidence: 98%
“…Thrombin receptor-activating protein (TRAP), a 14-amino acid peptide identical sequence to the new amino-terminus derived from the thrombin-mediated cleavage, is a potent thrombin receptor activator [15]. We have previously reported that platelets stimulated by TRAP lead to the secretion of PDGF-AB [16] and that TRAP-induced activation of Akt in addition to p38 MAP kinase positively regulates the release of phosphorylated heat shock protein 27 (HSP27) from human platelets in patients with DM [17].…”
Section: Introductionmentioning
confidence: 99%
“…GTP-binding Rac was immunoprecipitated using a Rac1 Activation Assay Kit as described in the manufacturer's PLOS ONE instruction manual. The immunoprecipitated GTP-binding Rac and pre-immunoprecipitated lysates, that is total Rac, were subjected to Western blot analysis using antibodies against Rac [41].…”
Section: Analysis Of Rac Activationmentioning
confidence: 99%